The Quality of Life and Mental Health in Children with Primary Immunodeficiency - Binay Kayan Ocakoğlu; Neslihan Edeer Karaca; Güzide Aksu; Serpil Erermiş (Journal of Pediatric Research, 2019)

(untitled)
Primary immunodeficiency disorders (PIDs) are characterized by recurrent and numerous infections, autoimmune disorders, and malignancies. These diseases are a heterogeneous group that contains many disorders caused by the disruption of the immune system. Despite being seen rarely, PIDs lead to serious morbidity and mortality. Children and adolescents with PIDs are expected to have a higher prevalence of psychopathologies and a lower level of the health quality of life In this text, we aim to review and summarize the current literature.